2015
DOI: 10.1111/1754-9485.12286
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose positron emission tomography/computerized tomography in differentiated thyroid cancer management: Importance of clinical justification and value in predicting survival

Abstract: FDG PET/CT performed in follow-up more than 6 months from primary treatment completion adds value to clinical judgment and a prognostic marker of overall survival in thyroid cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
0
12
1
Order By: Relevance
“…It has been reported that FDG-PET/CT is also predictive of OS in DTC patients with high serum Tg or with advanced stage cancers, [ 13 , 24 ] while in our study only Tg normalized at short-term follow-up was predictive of OS: the 9-years OS was 100% in patients with Tg normalized at short-term follow-up and 72% in those without ( P < .05). The lack of predictive value of FDG-PET/CT for OS in the our results could be due to the relatively small of number of patients, which should be acknowledged as one of the limitations of our study together with its retrospective nature.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…It has been reported that FDG-PET/CT is also predictive of OS in DTC patients with high serum Tg or with advanced stage cancers, [ 13 , 24 ] while in our study only Tg normalized at short-term follow-up was predictive of OS: the 9-years OS was 100% in patients with Tg normalized at short-term follow-up and 72% in those without ( P < .05). The lack of predictive value of FDG-PET/CT for OS in the our results could be due to the relatively small of number of patients, which should be acknowledged as one of the limitations of our study together with its retrospective nature.…”
Section: Discussioncontrasting
confidence: 48%
“…It is well known that FDG-PET/CT is a useful tool to individuate metastases with higher malignant histological grade, [ 5 ] and thus in our study a positive FDG-PET/CT could represent an indicator of increased aggressiveness predicting relapses. On the other hand, FDG-PET/CT is able to exclude recurrence or metastases [ 24 ] and negative FDG-PET/CT could be predictive of a very good response to therapy. [ 25 ] Similar to our findings, other retrospective studies demonstrated that a negative FDG-PET would predict an excellent outcome despite an elevated Tg value.…”
Section: Discussionmentioning
confidence: 99%
“…RECIST evaluation after RAI (months) 10.2 ± 1.7 10.8 ± 0.9 9.9 ± 1.3 1.000 or other conventional chemotherapy (Haugen et al, 2016;Ito et al, 2014). During recent years, 18 F-FDG PET/CT parameters have been well studied in DTC (Marcus et al, 2015). Patients with positive 18 F-FDG PET/CT may be considered candidates for surgical intervention or external radiation therapy since FDG-avid lesions have been reported to seldom improve with RAI alone (Bannas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariate Cox regression model, factors associated with overall survival were stage ( P < 0.0001), time to scan ( P = 0.0005) and FDG‐PET/CT result ( P < 0.0001). The authors demonstrated that FDG‐PET/CT, performed at any time after treatment completion, is a significant predictor of overall survival in patients with DTC, especially in patients with advanced stage tumours …”
Section: Prognostic Role Of Fdg‐pet/ct Performed At Restaging/follow mentioning
confidence: 99%